Production of Ethanol from Ripe Plantain Peel Hydrolysate by Saccharomyces cerevisiae - Cyprian E. Oshoma; Ese Okojie; Bunmi B. Omorotionmwan (Journal of Basic & Applied Sciences, 2019)
Aim: Nigeria is amongst the largest Musa paradisiaca (Plantain) producing countries and ripe plantain peels are discarded as waste thus polluting the environment. Utilization of this agricultural waste to useful products like ethanol will be a welcome development. The influence of pretreatment on plantain peels hydrolysate for ethanol production by Saccharomyces cerevisiae and the effect of media supplementation were studied. Methodology: The pretreatment methods used before carrying out fermentation of the hydrolysate were acid, steam and alkali. Parameters analyzed in all the hydrolysates and during fermentation were cell number, pH value, ethanol, glycerol concentration and inhibitory compounds using standard procedures. Results: The results showed that acid pretreatment had the highest cell number, glycerol and ethanol concentrations of 27.30 ± 2.47 x 106 cells/mL, 4.43± 0.15 mg/mL and 12.31± 0.08 mg/mL respectively. Alkali pretreated plantain peel hydrolysate had the least values of 12.25 ± 1.77 x 106 cells/mL, 3.81 ± 0.10 mg/mL and 7.50 ± 0.21 mg/mL for cell number, glycerol and ethanol concentrations, respectively. There was a significant difference in ethanol production when comparing the acid pretreatment to the others (P < 0.05). The acid hydrolysate was optimized by supplementing the media and results showed that the cell number, glycerol and ethanol concentration slightly increased. Conclusion: It was observed that acid hydrolysate of plantain peels can be utilized economically as a cheap substrate for bioethanol production and the yield can be enhanced through media supplementation.